Multi-structure Cortical States Deduced From Intracellular Representations of Fixed Tactile Input Patterns - Norrlid, Johanna; Enander, Jonas M. D.; Mogensen, Hannes; Jörntell, Henrik (Frontiers in Cellular Neuroscience, 2021)
The brain has a never-ending internal activity, whose spatiotemporal evolution interacts with external inputs to constrain their impact on brain activity and thereby how we perceive them. We used reproducible touch-related spatiotemporal sensory inputs and recorded intracellularly from rat (Sprague-Dawley, male) neocortical neurons to characterise this interaction. The synaptic responses, or the summed input of the networks connected to the neuron, varied greatly to repeated presentations of the same tactile input pattern delivered to the tip of digit 2. Surprisingly, however, these responses tended to sort into a set of specific time-evolving response types, unique for each neuron. Further, using a set of eight such tactile input patterns, we found each neuron to exhibit a set of specific response types for each input provided. Response types were not determined by global cortical state, but instead likely depended on the time-varying state of the specific subnetworks connected to each neuron. The fact that some types of responses were recurrent, i.e. more likely than others, indicates that the cortical network had a non-continuous landscape of solutions for these tactile inputs. Therefore, our data suggests that sensory inputs combine with the internal dynamics of the brain networks, thereby causing them to fall into one of multiple possible perceptual attractor states. The neuron-specific instantiations of response types we observed suggest that the subnetworks connected to each neuron represent different components of those attractor states. Our results indicate that the impact of cortical internal states on external inputs is substantially more richly resolvable than previously shown.